Sustained Contraction in Vascular Smooth Muscle by Activation of L-type Ca2+ Channels Does Not Involve Ca2+ Sensitization or Caldesmon - Ets, Hillevi K.; Seow, Chun Y.; Moreland, Robert S. (Frontiers in Pharmacology, 2016)
Vascular smooth muscle (VSM) is unique in its ability to maintain an intrinsic level of contractile force, known as tone. Vascular tone is believed to arise from the constitutive activity of membrane-bound L-type Ca2+ channels (LTCC). This study used a pharmacological agonist of LTCC, Bay K8644, to elicit a sustained, sub-maximal contraction in VSM that mimics tone. Downstream signaling was investigated in order to determine what molecules are responsible for tone. Medial strips of swine carotid artery were stimulated with 100 nM Bay K8644 to induce a sustained level of force. Force and phosphorylation levels of myosin light chain (MLC), MAP kinase, MYPT1, CPI-17, and caldesmon were measured during Bay K8644 stimulation in the presence and absence of nifedipine, ML-7, U0126, bisindolylmaleimide (Bis), and H-1152. Nifedipine and ML-7 inhibited force and MLC phosphorylation in response to Bay K8644. Inhibition of Rho kinase (H-1152) but not PKC (Bis) inhibited Bay K8644 induced force. U0126 significantly increased Bay K8644-dependent force with no effect on MLC phosphorylation. Neither CPI-17 nor caldesmon phosphorylation were increased during the maintenance of sustained force. Our results suggest that force due to the influx of calcium through LTCCs is partially MLC phosphorylation-dependent but does not involve PKC or caldesmon. Interestingly, inhibition of MLC kinase (MLCK) and PKC significantly increased MAP kinase phosphorylation suggesting that MLCK and PKC may directly or indirectly inhibit MAP kinase activity during prolonged contractions induced by Bay K8544.